Pengaruh Harga, Kemudahan, Kualitas Pelayanan Dan Kepercayaan Terhadap Keputusan Pengguna Jasa Gojek Di Kota Malang (Studi Kasus Pada Pengguna Jasa Gojek Di Kecamatan Lowokwaru Kota Malang) - Idatul Faizati; Rois Arifin; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2020)
Abstract The purpose of this study is to find out how Gojek users decide to use Gojek services. In this research, five variables are used, namely price, convenience, service quality and trust, which are independent variables, while user decisions are dependent variables. Whereas in this study the number of respondents obtained was 147 respondents based on the results of the questionnaire distributed but from that number there were 47 respondents who did not meet the sample criteria, so the number of samples that had been selected was only 100 respondents. In determining the sample criteria in this study using purposive sampling, namely determining the sample based on certain criteria. The analysis technique used in the study is multiple linear regression analysis technique that is with research data in the form of cross section data. The results in this study indicate that the variable price, convenience, service quality and trust simultaneously have a positive effect simultaneously on Gojek service user decisions. On the price variable, convenience, service quality and trust have a partial positive effect on the decision of Gojek service users.Keywords: Price, Ease, Service Quality, Trust, User Decision.